Floors number influence on the instability parameter of reinforced concrete frame-braced buildings - ELLWANGER,R. J. (2019)
Abstract This work aims to investigate the floors number influence on the instability parameter limit α1 of reinforced concrete frame-braced buildings; it succeeds another work in this field of knowledge, in which the same question was investigated for wall- and core-braced buildings. Initially, it is showed how the ABNT NBR 6118:2014 (Brazilian code for concrete structures design) defines when a second order analysis is needed. Topics concerning to physical nonlinearity consideration and to the lateral deflection components of frames are also presented. It follows an analytical study that led to the derivation of a method for determining the limit α1 as a function of the floors number and the relation between bending and shear stiffness. Finally, some examples are presented and their results are used for checking the method accuracy.